Mechanism of Gift-Giving through Diplomatic Letters from the Bima Sultanate to the Netherlands: (Mekanisme Pemberian Hadiah sebagai Pengerat Hubungan Diplomatik dalam Warkah Kesultanan Melayu Bima kepada Belanda) (Malay Literature, 2021)
The Bima Sultanate is one of the Islamic kingdoms that had close relations with the Netherlands. This relationship was established and became more vibrant when Bima was ruled by Sultan Abdul Hamid. Sultan Abdul Hamid was an active monarch when it came to managing Bima's relations with the Netherlands. The relationship was strengthened through the sending of epistles which were an important medium for sending messages at the time. Thus, this article will identify diplomatic epistles from Bima to the Netherlands, as well as analysing the accompanying gifts. This article uses the library research method and utilizes the Theory of Islamic Diplomacy of Ahmed Musa (2009). The results show that there is a diversity of gifts given by Bima to the Netherlands in order to strengthen the relationship between the two kingdoms. This study hopes to contribute to the research and study of epistles from the Malay sultanates, and thereby to encourage new findings, as well as the development of new knowledge about epistles from Malay sultanates.Keywords: Bima, Netherlands, letters, Malay, diplomatic